Russia and South Ossetia: conferring statehood or creeping annexation?. Issue 1 (2nd January 2016) - German, Tracey
Abstract: Events in Ukraine have distracted international attention from the ongoing Russian involvement in the unresolved conflicts of the South Caucasus. This article explores the intensification of relations between South Ossetia and Moscow, focusing on the extent to which South Ossetia exists as a functioning state entity. Are the authorities in Tskhinvali able to provide vital services such as defence and control over 'state' borders and territory without Russian involvement? What has been happening in South Ossetia is important, despite being overshadowed by events in Ukraine, as it is indicative of what may well occur in eastern Ukraine: a simmering separatist conflict that is far more than a domestic territorial dispute, with both regional and international implications.